Effect of the Addition of Essential Oils and Functional Extracts of Clove on Physicochemical Properties of Chitosan-Based Films - Paola Reyes-Chaparro; Nestor Gutierrez-Mendez; Erika Salas-Muñoz; Juan Guillermo Ayala-Soto; David Chavez-Flores; León Hernández-Ochoa (International Journal of Polymer Science)
Mechanical and barrier properties of chitosan films prepared with essential oils of clove and functional extract were studied. The films made with functional extracts (esters E6 and E7) presented the significant increment of extensibility compared with the untreated chitosan films. In the case of punction test, the films made with the esters E6 and E7 resisted more the applied strength before tearing up compared with the chitosan control film (without any treatment). Thermogravimetric analysis values were determined for the chitosan control film and chitosan film treated with clove essential oil obtaining 112.17°C and 176.73°C, respectively. Atomic force microscopy (AFM) was used to determine their morphology by analyzing their surfaces and phase arrangement; AFM was also used to observe the porosity in chitosan-based antimicrobial films and the chitosan films incorporating functional extracts. The water vapour permeability (WVP) data showed that incorporating the functional extract to the formulation of films has a positive effect on water vapour barrier properties. In general, the incorporation of essential oils and functional extract of clove at 20% in chitosan films caused microstructural changes that were dependent on the different affinity of components.